African Fellowships for Research in Indigenous and Alternative Knowledges (AFRIAK) Selection Report: CODESRIA Bulletin Online, No. 10, September 2025 - Secretariat, CODESRIA (CODESRIA Bulletin, 2025)
Introduction The African Fellowships for Research in Indigenous and Alternative Knowledges (AFRIAK) is a collaboration resulting from a discussion between CODESRIA and Mastercard Foundation. The discussion goes back to 2021, when CODESRIA reached out to Tade A. Aina, then Head of Research and Senior Director: Research and Learning at Mastercard Foundation, to consider support for research and policy impact initiatives at CODESRIA. Although the thematic focus was not clear at the meeting, it soon zeroed in on the mutual interest that CODESRIA and the Foundation shared in Indigenous knowledge systems (IKS). Between that meeting and 2024, a range of discussions were held to concretise the initiative and frame a concept note that would encapsulate the mutual interests of the two organisations in supporting work on the dynamic between IKS, the youth and livelihood opportunities that this intersection offers. The culmination was the official launch of AFRIAK in November 2024. AFRIAK is a three-year research and mentorship programme implemented in partnership with the Mastercard Foundation. It aims to broadly strengthen the research and training ecosystem in Africa by focusing on IKS as a thematic area and seeking to support the education and skilling of young people to undertake research based on Indigenous and endogenous knowledge perspectives.[1] It is envisaged that this project will enable the application of Indigenous Knowledge perspectives and evidence to promote growth in priority sectors and spur economic activities led by young people as a source of dignified livelihoods for themselves and their communities. Ultimately, AFRIAK seeks to recentre the contribution of Indigenous and alternative ways of knowing, in the quest for Africa’s social transformation. Embedded in the project conceptualisation is a desire to change how knowledge is produced, with an emphasis on the co-production of knowledge rather than on the existing processes that advance a rather exploitative and extractive approach by researchers to bearers of Indigenous Knowledge. In designing the project, the Council was cognisant of the pejorative baggage that the notion ‘Indigenous’ carried. Previous research at CODESRIA, led by the Beninois philosopher, Paulin Hountondji, located the problematic use of the notion in its colonial heritage and persisting scientific dependence in Africa today.[2] In colonised societies, ‘indigenous’ was contrasted with ‘exotic’, implying that the former was native, traditional, primitive and resistant to change. Indigenous knowledge (IK) was thus framed as vernacular, uncivilised, deprived and superstitious. Hountondji analysed these forms of knowledge, noting that the pejorative connotations made sense only in contexts of persisting extraversion of knowledge in Africa.[3] He preferred the notion of ‘endogenous’ to ‘Indigenous’, arguing that this reframing would recentre Africa in knowledge production. In response, AFRIAK, while acknowledging these debates and the historical baggage many terms carry, uses the notion ‘Indigenous Knowledge’ to refer to what is organic to society, to borrow Gramsci’s concept of the organic intellectual. It underscores the idea of ‘using what we have’, while recognising that what we have in society is not static nor does it exist in splendid isolation from numerous other influences; rather, it evolves through continuous interaction with other knowledge systems.[4] AFRIAK will be implemented over a period of three years with the hope that this can be extended to a ten-year programme. Its primary target is young Africans under the age of 35 years. AFRIAK is prioritising young Africans who currently reside on the continent partly because they have the immediacy of contact with communities but also because young Africans resident on the continent suffer challenges very specific to their contexts. The first year of the programme set out to recruit 100 fellows. In addition, CODESRIA committed that 70 per cent of the fellows admitted into the programme for each of the three years would be young women under the age of 35. In daring to set such a high standard of gender equity for AFRIAK, the Council aimed to change the narrative in which the absence of female applicants in similar programmes, in the Council and beyond, had been turned into a confirmation that there are, in fact, no female applicants to fill the vacancies advertised for such a programme. As this report documents, the response surpassed the 70 per cent threshold. To achieve these goals, the Council disseminated widely the 2025 AFRIAK call for proposals on 15 March 2025, with a submission deadline set for 15 May 2025. The response to this inaugural call was overwhelming, reflecting both the demand for opportunities of this kind and the vibrant interest in emerging scholarship in Indigenous Knowledge systems across the continent. This interest in this scholarship was already visible to attentive observers in countries like South Africa, Mali, Benin, Nigeria and Ethiopia, to name but these few. This report provides a detailed account of the selection process that commenced soon after the submission deadline. The end goal of the selection process was the recruitment of the inaugural cohort of fellows to be inducted into the programme in 2025. Although the original target was 100 fellows, after a sequenced selection process a total of 150 fellows from an initial pool of 861 applicants were selected. As envisaged, 70 per cent of the selected fellows were young women. The selected fellows are drawn from 32 African countries spread across the continent’s core five regions (North, West, Central, Eastern and southern Africa). The Selection Process The 2025 AFRIAK Fellowship selection process proceeded in four stages, with premium being paid to the quality of applications submitted and the diversity needed for the cohort of successful applicants. The initial process involved screening the applications to remove multiple and dummy submissions (applications with no substantive content in all their accompanying attachments). In the end, the Council retained a total of 609 valid applications submitted in response to the 2025 AFRIAK call for proposals. These comprised 521 individual submissions and 88 group submissions. Collectively, these represented a total of 861 applicants. The diversity of these applications is indicative of the opportunities that this fellowship programme provides. Of the 861 applicants, 432 were women and 429 were men, reflecting an almost even gender distribution. Figure 1 summarises the results. The geographic distribution of the applicants demonstrates a spread across 39 African countries and 5 non-African countries, with 3 applicants holding dual citizenship. Table 1 provides a detailed breakdown of applications by country; Figure 2 illustrates the percentage distribution across the five African regions. Figure 1: 2025 AFRIAK applications—Gender composition (View PDF file) Table 1: 2025 AFRIAK applications—Distribution by country (View PDF file) Figure 2: 2025 AFRIAK applications—Regional distribution (View PDF file) Subsequently, the selection process focused on ensuring that the applications met the basic requirements of eligibility as outlined in the call for proposals. All 609 applications were screened to remove applications deemed ineligible. These included: Applications from applicants older than the stipulated age limit of 35 years as of 2025. All applicants born before 1990. Applicants who did not provide their date of birth in any of the documents submitted. Applications that had no concept note attached or those for which the concept note was not related to the theme of Indigenous Knowledge. Applicants whose institutional affiliation was outside the African continent. Following this assessment, of the total 609 applications considered, 458 applications (75 per cent) were deemed eligible to be submitted for external evaluation. Of the eligible applications, 377 were individual submissions while 81 were group submissions. In total, these represented 700 applicants. The gender composition of applications after screening remained steady, with female applicants constituting 54 per cent of the eligible applicants. Figure 3 provides a visual illustration of this overall distribution; Figure 4 and Figure 5 break down the gender composition by individual and group submissions. The geographic distribution of applications after screening reveals a spread across 39 nationalities—38 being African nationalities and one being non-African (French). Table 2 and Figure 6 illustrate the country and regional spread respectively. Figure 3: 2025 AFRIAK applications—Gender composition of total applicants who met the basic criteria set out in the call for proposals (View PDF file) Figure 4: Gender composition of individual applicants who met the basic criteria set out in the call for proposals (View PDF file) Figure 5: Gender composition of group applicants who met the basic criteria set out in the call for proposals (View PDF file) Table 2: Country spread of applicants who met the basic criteria set out in the call for proposals (View PDF file) Figure 6: Regional distribution of applicants who met the basic criteria set out in the call for proposals (View PDF file) The thematic focus of the proposals also reveals an interesting pattern. The call for applications identified 13 Indigenous Knowledge (IK)-related themes under which concept notes could be submitted. The assessment conducted at this stage revealed that the themes of ‘Indigenous Knowledge and Climate Change’ and ‘Indigenous Medical Science and Practices’ attracted the highest number of submissions, with 79 and 77 applications respectively. While submissions across all 13 themes were relatively balanced, many concept notes addressed multiple overlapping thematic areas. For purposes of refining the data presented in Table 3, each concept note was classified under the one theme that most closely reflected its primary focus. During the development of the AFRIAK proposal, a deliberate decision was taken to align the areas of thematic focus with the desire to elicit as many proposals as possible from female applicants. The idea was to engage female applicants via thematic areas where women play a significant role. It is unclear at this stage if the pattern of application reflects success in the alignment the Council envisaged, but it is clear that the thematic distribution allows for the Council to attain effective female engagement with this area of work. Table 3: Thematic focus of applications that met the basic criteria set out in the call for proposals (View PDF file) The 458 eligible applications were submitted in three languages—English, French and Portuguese. Applications in English constituted the bulk of submissions (79 per cent), followed by submissions in French (21 per cent), while only one submission was received in Portuguese. The language of submission at this stage, like the previous stage, did not necessarily correspond to the applicants’ linguistic identity—understood here to mean the Anglophone, Francophone and Lusophone linguistic demarcations. For instance, some applicants from Francophone and Lusophone communities chose to submit their applications in English. Consequently, although the language of submission provides a useful data point, it is not a definitive representation of the linguistic composition of applicants. It merely reflects the versatility of the research community being targeted. The evaluation of all 458 eligible applications was conducted by an independent panel of 8 reviewers. The evaluation exercise was designed to ensure objectivity and uphold the scientific quality of the final set of concept notes selected. The committee of 8 academics convened in Nairobi, Kenya from 16–19 July 2025 in a conducive environment suitable for the exercise of reviewing the applications. The team of reviewers were inducted into the exercise through a session with CODESRIA staff. During the meeting, the Mastercard Foundation’s Director of Research Systems Strengthening and Knowledge Mobilization, Ayo Ojebode, was invited to give an overview of what the project was about from the perspective of the Foundation. Noting that the Mastercard Foundation had, since 2018, shifted 70 per cent of its operations from Canada to Africa, with presence in Nigeria, Ghana, Senegal, Ethiopia, Kenya, Uganda and Rwanda, he pointed out that the Foundation’s goal was to enable 30 million African youth to access opportunities by 2030, with 70 per cent of these opportunities targeted at women. The Foundation’s commitment to having 70 per cent female participation across all programmes it supports was its attempt to correct some of the historical and cultural injustices of the past. This conviction underpinned both the AFRIAK project and the Foundation’s interest in advancing Indigenous Knowledge. Ayo underscored that the aim of AFRIAK was to create a space for African scholars to explore deeply African knowledges and practices that speak to Africa’s problems. He highlighted three key interventions that would shape AFRIAK’s approach. Intergenerational approach: Recognising that the injustices spanning 500 years could not be resolved within a single generation, AFRIAK sought to establish a platform for young African scholars under the age of 35, to engage in research on Indigenous and multigenerational knowledge. Their work would be guided and supported by experienced scholars and community knowledge-holders, ensuring the transfer of skills, mentorship and continuity across generations. Balanced knowledge relationships: Historically, research on Indigenous Knowledge has been extractive, with scholars gathering insights from communities without reciprocity. AFRIAK sought to correct this imbalance by fostering relationships of fairness and collaboration. University professors would collaborate with community knowledge-holders to jointly mentor young researchers. This co-production model is intended to create an equitable space, where all forms of knowledge are respected, validated and applied. Institutional strengthening: The sustainability of Indigenous Knowledge depends on strong institutions. Although Africa hosts many intellectual hubs committed to this agenda, many remain fragile and overly reliant on their founders. AFRIAK would work to identify, support and strengthen these hubs, departments, associations and community-based groups, to ensure they endure beyond individual leaders and contribute meaningfully to the long-term task of redressing historical marginalisation. The induction of the reviewers from CODESRIA situated AFRIAK within the Council’s longstanding interest in endogenous and Indigenous Knowledge, recalling earlier work in the 1980s and 1990s under the leadership of the late Prof. Paulin J. Hountondji, when the Council critiqued the marginalisation of African knowledge in the global library and the dependence on external scientific paradigms. AFRIAK marked an important milestone in CODESRIA’s partnerships and presented an opportunity to renew the Council’s intellectual leadership in this field. Three key commitments would define AFRIAK’s implementation: Epistemological commitment: AFRIAK was a deliberate push to encourage African universities to embrace forms of knowledge not canonised in Western traditions, thereby expanding methodologies of knowledge validation. Co-production of knowledge: By fostering equitable collaboration between academics and Indigenous Knowledge-holders, AFRIAK aimed to correct the pattern whereby scholars extracted knowledge from communities without paying any attention to reciprocity. Commitment to gender equity: AFRIAK was firmly anchored on achieving 70 per cent female participation among fellows. The Council acknowledged the often-contentious nature of the term ‘Indigenous’. To guide the AFRIAK programme and provide conceptual clarity, CODESRIA committed to developing a concept note that would be informed by African perspectives and the wider literature on Indigenous and endogenous knowledge. The 2025 AFRIAK Applications Evaluation Framework The Council shared an evaluation framework with the reviewers that was based on a structured assessment of the three core documents submitted in response to the call for proposals. These documents included the concept note, the CV and reference letters. Each document served a specific function in demonstrating the applicant’s potential to contribute meaningfully to the AFRIAK programme. The evaluation was guided by an elaborate set of guidelines and a standardised scoring form. Based on the guidelines, reviewers were required to assign to each application a consolidated score ranging from 0 to 100 per cent. This score was broken down into a maximum of 20 per cent for the CV, a maximum of 60 per cent for the concept note and a maximum of 20 per cent for the reference letters. Reviewers agreed that scientific quality would be the primary criterion, after which diversity considerations such as gender, language and regional balance would be considered in informing the final selection. An initial pass mark of 50 per cent was set, meaning all applications above 50 per cent qualified to be considered for the final selection. The results of the evaluation were shared and discussed at a final meeting of the review team convened on 19 July 2025. The Secretariat presented the consolidated results of their evaluations as seen in Table 4. Table 4: Consolidated results of reviewed applications (View PDF file) The initial pass mark of 50 per cent resulted in a total of 307 applications qualifying for consideration in the final selection. Given the large number, the reviewers agreed to revise the threshold upwards to 60 per cent. Consequently, only applications that scored 60 per cent and above were eligible to be considered for final selection. In total, 242 applications met the revised benchmark of 60 per cent and above. These included 190 individual submissions and 52 group submissions, representing 365 applicants spread across 33 African countries. Women accounted for 58.3 per cent of those who scored above 60 per cent. By language, applications written in English dominated, with 87 per cent (210 applications), while applications in French accounted for 13 per cent (32 applications). Table 5 provides the results of the assessment by country. Table 5: Country spread of applicants who met the 60 per cent and above pass mark (View PDF file) General Reviewer Feedback Following the presentation of the results, the reviewers shared their overall impressions of the applications and the review process. Several key insights emerged that will be critical in refining future selection processes and informing the design of subsequent calls. The feedback focused on: 1) the applications; 2) emerging regional patterns of applications; 3) other positive comments worth noting. We discuss each in turn. The applications Regarding the observations on the applications, the following five issues were raised. The reviewers invited the Council to be clear in future calls for proposals what institutional affiliation meant and was admissible for the fellowship. They recommended clearer guidelines on what constitutes affiliation to research, academic and Indigenous Knowledge institutions. They noted that some ambiguity exists between being a member of an organisation and having formal institutional affiliation, and among other challenges this affected how scores were assigned with respect to this category. The reviewers also raised concerns about reference letters, pointing out the poor quality of many reference letters, with most being very generic and failing to link the applicants to their concept notes. In some cases, reference letters appeared plagiarised or possibly AI-generated, thereby undermining their credibility. The reviewers also indicated that many concept notes had serious methodological gaps that went against the commitment to co-produce knowledge. Many applications, proposed to ‘enter communities’ and extract Indigenous Knowledge without specifying clear collaborative or participatory methodologies. This misalignment highlights broader problems in methodology training, which that do not sensitise student to the complementarity that research requires. They agreed that an urgent need exists for dedicated African-led methodology training workshops, to help young scholars bridge the methodology gaps created by university training. Notable similarity and overlap in proposals was also remarked on. A number of applications, admittedly few, showed strong similarities, raising concerns about originality and the need for a plagiarism detection mechanism to screen proposals. A distinction was made between AI-assisted writing and AI-generated writing, with the Council tasked to reflect on how best to navigate the distinction in this emerging AI era. There was a consensus that the final selected applications would be subjected to a plagiarism test to weed out AI-generated writing and plagiarism. Finally, the ethical concerns. Some proposals included ethically sensitive activities, such as asking communities to re-enact initiation rites, which could expose private cultural practices. Reviewers stressed the importance of embedding ethical safeguards and ensuring respect for Indigenous communities. Regional patterns Regarding regional patterns, the following three issues were raised. Francophone vs Anglophone divide: The reviewers who assessed the concept notes written in French noted a persistent methodological weakness in applications from French-speaking countries. The theoretical framing and writing structure were often weaker in comparison to submissions from English-speaking countries. Suggestions included targeted capacity-building for Francophone scholars. Prevalence of themes in certain regions: For example, in proposals from West Africa, food security and climate change themes predominated; proposals from Eastern Africa were centred on traditional medicine; those from southern Africa focused more on self-awareness, healing and university-based IKS initiatives. This regional clustering presents an opportunity for cross-country collaboration and knowledge sharing. ‘Overrepresentation’ of some countries and diversity: Applicants from countries like Nigeria and Kenya dominated the pool. To ensure that other countries were not overshadowed, it was agreed that a proportional representation system would be applied. In addition, the Council took note that a number of applications had been received from countries historically underrepresented in CODESRIA programming, including Tanzania, Benin and Senegal. Of course, it was great to see applications from Libya and Somalia. Other positive comments In addition, the reviewers identified three notable positive observations. Articulation of African identity: Reviewers were impressed by how many applicants freely expressed their African identity, consciously resisting Eurocentric frameworks. It was clear that this programme was perceived by applicants as creating a safe intellectual space for young scholars to reclaim and articulate African-centred knowledge. High quality and volume of female applicants: Applications from female applicants were described as in ‘a class of their own’, often producing imaginative, observant and detailed proposals that stood out in creativity and rigour. It was clear from discussions that the Council would achieve its targeted 70 per cent female participation without deploying any affirmative action intervention. Innovative/non-mainstream applicants: Many applicants to CODESRIA programmes are graduate students or PhD holders, so the reviewers were pleased to come across applicants outside these traditional constituencies. These included young people with a first degree only, as well as young people who integrated Indigenous Knowledge-bearers and community elders as referees or mentors. The Way Forward Based on the scores and the discussions that followed among reviewers, a consensus was adopted to guide the way forward in the selection of final applicants to be invited to the fellowship. These were also understood as instructions to the CODESRIA Secretariat to conclude the process. The reviewers agreed to peg the pass mark of 60 per cent as the minimum threshold. No application below this would qualify to be included in the final list of qualified applications to be considered for the fellowship. The only exceptions would be strong proposals that fell short of the pass mark because of technicalities such as weak reference letters or the lack of reference letters. In view of the overwhelming number of qualified applications, the reviewers urged CODESRIA to request Mastercard Foundation to increase the number of fellows from 100 to 150 for the first-year cohort. This can then be adjusted accordingly with the second and third cohorts. The convening agreed that the final selection would have at least 70 per cent female applicants. In addition to the scores and the commitment to have 70 per cent female participation, the final selection would consider other diversity considerations, including nationality, language and thematic spread. All final selected concept notes would undergo a plagiarism check prior to confirmation. Based on the above stipulations, the Secretariat was mandated to select the final fellows from the pool of applicants who scored above 60 per cent. Final Selection In the final stage of the selection process, the Secretariat focused on ensuring that the final cohort reflected both the quality of submission mandated for the cohort and the diversity targets that AFRIAK ought to represent. A final assessment of the 365 applicants who met the 60 per cent threshold was discussed in the Secretariat, and a decision was taken, with the support of the Mastercard Foundation, to increase the final number of selected applicants for Year 1 cohort from 100 to 150. A total of 115 applications, representing 150 fellows—70 percent of whom are young women—were selected to form the inaugural AFRIAK cohort. Table 6, Table 7, Figure 7, Figure 8 and Figure 9 provide a detailed breakdown of the fellows by country, region, gender, theme and language. Table 6: Country spread of the 2025 AFRIAK inaugural cohort (View PDF file) Figure 7: Regional distribution of the 2025 AFRIAK inaugural cohort (View PDF file) Figure 8: Gender composition of the 2025 AFRIAK inaugural cohort (View PDF file) Table 7: Thematic focus of projects of the 2025 AFRIAK inaugural cohort (View PDF file) Figure 9: Language of submission of the 2025 AFRIAK inaugural cohort (View PDF file) The Induction Workshop The culmination of the selection process is the convening of an induction workshop for all the recruited fellows. The workshop is scheduled to take place in Kigali, Rwanda from 30 September to 11 October 2025. The workshop will focus on inducting the fellows into the methodological, theoretical and ideological issues around indigeneity, and Indigenous Knowledge systems; methods of moving research to become action- or policy-engaged; digital curation; and connecting the fellows to mentors. 1 The coupling of Indigenous and endogenous is deliberate, to signal an awareness of the pejorative sense in which the word Indigenous tends to be cast. This project is aware of this limitation and will offer some reflections on how the notion of Indigenous is employed. 2 Paulin Hountondji, ‘Scientific Dependence in Africa Today’, in Research in African Literatures, Vol. 21, No. 3, 1990. 3 Paulin Hountondji, ‘Recherche et extraversion: éléments pour une sociologie de la science dans les pays de la périphérie’, in Africa Development / Afrique et Développement, Vol. 15, No. 3/4, 1990. 4 There are similar discussions along these lines led by Yuen Yuen Ang, the Alfred Chandler Chair Professor of Political Economy at Johns Hopkins University and author of the How China Escaped the Poverty Trap.